UPAYA MENINGKATKAN MINAT BELAJAR SISWA KELAS IV MELALUI MEDIA PEMBELAJARAN INTERAKTIF WORDWAALL DI SDN BUNDER IV - Nurhidayat, Adelia Putri; Fajar Nugroho, Oktian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low student learning interest has become a fundamental challenge at SDN Bunder IV, where approximately 77.42% of 31 students in Grade IV A appeared passive due to the predominance of non-varied lecture-based methods. This study aims to improve fourth-grade students' learning interest in Science and Social Studies (IPAS) through the implementation of Wordwall interactive learning media. The research employed a Classroom Action Research (CAR) design using the Kemmis & McTaggart model, conducted across two cycles comprising planning, action, observation, and reflection phases. The research subjects were 31 students of Grade IV A. Data were collected through a Likert-scale learning interest questionnaire, observation sheets, and semi-structured interviews, and analyzed using descriptive statistics and N-Gain scores. Results demonstrated significant improvement from Cycle I to Cycle II: teacher activity increased from 89% to 97%, student activity from 89% to 96.5%, and learning interest from 90% to 97%. Post-test mastery in Cycle II reached 93% with an average score of 91, while the N-Gain value improved from the low category (0.25) to the moderate category (0.37). This study concludes that Wordwall media effectively enhances student learning interest and active participation. It is recommended that teachers utilize Wordwall features variably, supported by Student Worksheets (LKPD) and adequate technological infrastructure at school.